Determinants of 3G Adoption in Malaysia: A Structural Analysis - Chong, Alain Yee Loong; Ooi, Keng Boon; Darmawan, Nathan; Lee, Voon Hsien (Taylor & Francis, 2010)
The main aim of this paper is to examine the factors that affect consumers’ decisions to adopt 3G. The factors that are studied in this research include perceived ease of use (PEOU), perceived usefulness (PU), perceived cost (PC), social influence (SI), self efficacy (SE), privacy and security (PS), and fun or enjoyment (FE). The collection of data comprises of 371 mobile phone users in Malaysia. Structural equation modelling was applied to test the hypothesis developed in this research study. The findings from this study indicated that PU, SE and PS have a significant impact on consumers’ decision to adopt Third Generation (3G). There are several implications from this study. Firstly, this study focuses on 3G adoption in a fast growing, developing country. Secondly, our study has also extended traditional TAM models by incorporating additional variables related to culture. As many developing countries are starting to embrace 3G technology, our study allows the government as well as service providers of these countries to formulate appropriate business strategies based on our study.